Translation Competence in Translator Training Programs at Saudi Universities: Empirical Study - Hazaea Abduljalil Nasr; Qassem Mutahar (De Gruyter, 2024)
This study aims to investigate the manifestations of instrumental translation competence (ITC) in translator training programs in six Saudi universities. It explores students' knowledge and skills in ITC in terms of training and translation courses, translation tools, and usage patterns, drawing on the PACTE group of translation competence. In this empirical study, the data were collected from the documents of program and course specifications at translation programs in six Saudi universities, utilizing a checklist to analyze the manifestations of ITC in the targeted programs. Further, an open-ended questionnaire was utilized to identify translation students' perceptions of ITC in such programs. While the open questions were analyzed using thematic analysis, the closed questions were analyzed quantitatively. The study found that the translation training programs include translation technology courses, albeit to a lesser extent, including only one or two translation technology courses within the entire 4-year program. The main emerging themes from the students' responses are enhancement, level of experience, and utilization of ITC. The analysis also revealed a lack of training in translation technology, a lack of knowledge of advanced translation tools, their awareness of the impact of translation tools on translation quality, and inappropriate use of translation tools.